Next generation sequencing detection in archival surgically resected lung adenocarcinoma specimens harboring the anaplastic lymphoma kinase fusion protein - Zhiming Jiang; Chenghui Li; Hongyang Lu (Journal of the Pakistan Medical Association, 2020)
Objective: To analyse clinical and molecular features in patients with surgically resected patients with lung cancer harbouring anaplastic lymphoma kinase fusion. Methods: The retrospective study was conducted at Zhejiang Cancer Hospital, Hangzhou, China, and comprised data from November 2013 to August 2015 of lung cancer patients. Anaplastic lymphoma kinase, epidermal growth factor receptor, kirsten rat sarcoma viral oncogene, v-raf murine sarcoma viral oncogene homolog, REarranged during Transfection proto-oncogene, c-ros oncogene 1 receptor kinase, V-Erb-B2 avian erythroblastic leukaemia viral oncogene homolog 2 and mesenchymal epithelial transition factor were noted using next generation sequencing. Clinicopathological parameters were also investigated. All patients were followed up till August 10, 2017. Data was analysed using SPSS 22. Results: Of the 19 patients, 15(79%) were non-smokers. Anaplastic lymphoma kinase rearrangements occurred in the acinar predominant in 6(31.6%), Continuous...